2020
DOI: 10.3390/microorganisms8091322
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Shelf-Life of Fresh Pasta Using Chickpea Flour Fermented with Selected Lactic Acid Bacteria

Abstract: Fresh pasta is subjected to rapid spoilage, mainly due to the metabolic activity of bacteria, yeasts, and especially molds, which negatively affect the sensorial characteristics and the safety of the product. In this work, chickpea flour was fermented with selected lactic acid bacteria, characterized in terms of the antifungal activity, and used to fortify fresh semolina pasta. Pasta was characterized and subjected to a long period of storage after being artificially inoculated with Penicillium roqueforti. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
1
9
0
1
Order By: Relevance
“…A decrease in OCT and the increase of cooking loss were indeed observed, regardless the fermentation pretreatment. Nevertheless, fortified pasta was characterized by hardness significantly higher than semolina control, according to previous findings [7][8][9][10].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A decrease in OCT and the increase of cooking loss were indeed observed, regardless the fermentation pretreatment. Nevertheless, fortified pasta was characterized by hardness significantly higher than semolina control, according to previous findings [7][8][9][10].…”
Section: Discussionsupporting
confidence: 79%
“…Twelve sensory attributes (described in Supplementary Table S2) were included in the lexicon [9]. Evaluation was carried out using a line scale from "not at all" (0) to "very" (10). Samples were analyzed after cooking at corresponding OCT and randomized distributed to the panelists, in duplicate.…”
Section: ∆E * Ab =mentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional and functional value of these gluten-free seeds can be enhanced by malting, cooking or fermentation [26,27]. Beverages, pasta [28,29], bread and sourdough were successfully made using the above-mentioned pseudocereals and legumes [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar approach, lactic acid fermentation of African nightshade leaves not only increased the shelf life but also the antioxidant activity and the bioavailability of flavonoids [ 2 ]. Schettino et al [ 3 ] showed that addition of fermented chickpea flour to fresh pasta provided better nutritional properties. Moreover, chickpea sourdough was efficient in limiting the development of yeasts and molds and, to a lesser extent, of enterobacteria, hence increasing the shelf life.…”
mentioning
confidence: 99%